Clinical management of chemotherapy for elderly gynecological cancer patients. Issue 7 (21st April 2021) - Yoshida, Yoshio; Inoue, Daisuke
Abstract: Aim: Since there are no established guidelines for the treatment of gynecological cancer in the elderly, medical treatment policy is currently decided by discussion with patients and their families based on doctors' experiences, referring to data from nonelderly patients and healthy elderly patients. The aim of this review was to clarify the current position of chemotherapy for elderly gynecological cancer patients and discuss the problems to be addressed in the future. Methods: Little evidence has been accumulated for anticancer drug treatment in elderly individuals with gynecological cancer. This review presents outlines and representative papers on general cancer chemotherapy for the elderly, and problems that need to be solved in gynecological cancer fields in the future are identified. Results: In 2018, the American Society of Clinical Oncology (ASCO) published guidelines for "Practical Assessment and Management of Vulnerabilities in Older Patients Receiving Chemotherapy: ASCO Guideline for Geriatric Oncology Summary". This guideline emphasizes that, when administering chemotherapy to patients over 65 years of age, vulnerabilities should be identified using geriatric assessment (GA). However, there have been no reports of clinical studies using GA in patients with cervical or uterine cancers, and only a few clinical studies using GA have been reported in patients with ovarian cancer. Conclusions: Scoring systems suitable for elderly Japanese patients remain lacking. A Japanese gynecological GA needs to be developed in cooperation with other disciplines.